Effects of standardized body placement in selected stretch protocols on flexibility and strain rates in athletes - Murgia, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Conflicting research reports fuel the debate about the benefits of stretch protocols.1,2,3,4 Effects of frequency, duration, temperature, and mechanical response to stretching have been examined.5,67,8,9,10 Nevertheless, The American College of Sports Medicine has sited a need for strategies to enhance the effectiveness of stretching on flexibility. The purpose of this study was to examine the effects of standardized body placement (SBP) in static and PNF stretching protocols on flexibility and strain rates in college athletes. Methods Male subjects (n=200) from college athletic teams were followed for 2 years. The athletes, who were "starters", were randomly assigned to static or PNF protocols. Half of the subjects in each of the protocol groups were randomly assigned to a sub-group in which strict adherence to body placement was required. All of the stretching "treatments" included a warm-up. The sit & reach test and a goniometer were used to measure trunk flexion, ankle dorsiflexion, hip extension, flexion, abduction, and lateral rotation at the end of the stretching session at various time intervals. Strain rates were recorded during the study's duration. ANOVA with Repeated Measured was used to analyze the data. Results Within-group comparisons indicated that both stretching techniques using SBP resulted in significant (p<.01) increases in flexibility at all time intervals. Between group comparisons demonstrated that both techniques incorporating SBP produced significant (p<.01) increases in flexibility when compared with un-standardized placement. Muscle strain rates were significantly (p<.01) decreased when SBP was incorporated. In addition, no differences were observed between static and PNF protocols across time. Discussion / Conclusions When SBP was performed to eliminate "cheating"; both static and PNF protocols significantly enhanced the flexibility of low back, thigh, and leg muscles. In addition, when SBP was incorporated into both stretch protocols, strain rates in intercollegiate athletes were significantly decreased. The results also indicate that there are no differences between static stretch and PNF protocol efficacy in short or long term.